1998
DOI: 10.2165/00007256-199825030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resistance Training on Endurance Performance

Abstract: In accordance with the principles of training specificity, resistance and endurance training induce distinct muscular adaptations. Endurance training, for example, decreases the activity of the glycolytic enzymes, but increases intramuscular substrate stores, oxidative enzyme activities, and capillary, as well as mitochondrial, density. In contrast, resistance or strength training reduces mitochondrial density, while marginally impacting capillary density, metabolic enzyme activities and intramuscular substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
1
17

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 54 publications
10
117
1
17
Order By: Relevance
“…To the best of our knowledge, the present study provides the first evidence that elite athletes have an augmented SOD capacity than recreationally active and sedentary control men. Although there is no definitive explanation for this discrepancy, but the notion that high maximal oxygen uptake (VO 2max ), which is a consequence of systemic endurance training (Tanaka and Swensen, 1998), are correlated to elevated antioxidant enzyme activity in other tissues (Jenkins et al, 1984), can explain some of the disparities in our study. These observations suggest that the fitness level of subject as well as the type and amount of exercise training could be taken into consideration when comparing antioxidant capacity of active people.…”
Section: Discussioncontrasting
confidence: 59%
“…To the best of our knowledge, the present study provides the first evidence that elite athletes have an augmented SOD capacity than recreationally active and sedentary control men. Although there is no definitive explanation for this discrepancy, but the notion that high maximal oxygen uptake (VO 2max ), which is a consequence of systemic endurance training (Tanaka and Swensen, 1998), are correlated to elevated antioxidant enzyme activity in other tissues (Jenkins et al, 1984), can explain some of the disparities in our study. These observations suggest that the fitness level of subject as well as the type and amount of exercise training could be taken into consideration when comparing antioxidant capacity of active people.…”
Section: Discussioncontrasting
confidence: 59%
“…Elastic bands can be used to strengthen certain muscle groups that machines cannot function in a certain muscle group, and also allow exercises to develop flexibility and balance (Selçuk, 2014).At the same time, in exercise with Thera-Band, we can say that only the speed and the number of repetitions can be changed to achieve weight loss, body tightness, general strength and conditioning. When the information in the literature is assessed, it is indicated that a well-planned combination of applied swimming and strength trainings are needed to improve strength training and swimming performance (Tanaka and Swensen, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, o organismo não conseguiria se adaptar a esses estí-mulos concorrentes de maneira adequada. Conseqüentemente, essa combinação de estímulos acarretaria prejuízo no processo crônico de adaptação ao treinamento físico (1,9,10) . As evidências experimentais que suportam essa hipótese são escassas (1) .…”
Section: Introductionunclassified